Biologia reprodutiva de Udu Momotus momota (Aves: Momotidae) - (:unkn) unknown (Universidade Estadual de Goiás, 2019)
Studies of the behaviors involved in the reproduction are of great importance for the conservation of the species and their respective habitats. Parental care in birds is expressed by a set of varied behaviors that results in three main activities: nest building, incubation, and offspring feeding. Despite the high energy costs in parental care activities, the life expectancy of the offspring increases. The present work was developed in the Municipal Natural Park located in Morrinhos - GO and had as objective to describe the reproductive behavior of Momotus momota, a Neotropical species that nests in cavities. The birds were monitored with binoculars (8X40) from 2011 to 2014. The results show that the species has biparental care, being that an individual stayed overnight with the eggs and also collaborated with daytime incubation, performing most of this activity (66%). The nestlings were observed from September to December, and they were fed by the couple at an average rate of 1.74 ± 0.29 feeding visits / nestling / hour, throughout the period they remained inside the nest. The omnivores diet was similar to that of the parents, being composed of different trophic groups, mainly insect (66%), fruit (19%) and worm (11%), as well as millipedes, spider, centipedes and vertebrates.

A seleção sexual é uma força que limita o acesso dos indivíduos de um sexo aos indivíduos do sexo oposto durante o período de reprodução, atuando conspicuamente nos machos e favorecendo tratos morfológicos e comportamentais que aumentam o sucesso reprodutivo. Muitas espécies de aves apresentam grandes diferenças sexuais, porém para muitas espécies consideradas monomórficas, pode haver pequenas diferenças entre machos e fêmeas. Os momotídeos são considerados monomórficos e o grupo é conhecido por apresentar uma longa e elaborada cauda com ápice em forma de raquete. O seu valor no reconhecimento dos sexos e na evolução de caracteres sexuais secundários ainda não foi pesquisado. Sendo assim, o objetivo geral do trabalho é verificar a ocorrência de caracteres sexuais secundários em Momotus momota e relacionar com o sucesso reprodutivo. As coletas de dados foram realizadas durante o período reprodutivo, de agosto a novembro de 2017 e 2018. Os casais de aves com ninhos ativos foram coletados com rede de neblina para medição de peso com balança de precisão e comprimentos com paquímetro ou trena. O reconhecimento dos sexos foi definido com base no resultado do exame de sexagem. Os resultados mostram que nos machos a massa, a área da bandeira e a área preta da bandeira são maiores e o tamanho da bandeira está relacionado negativamente com o sucesso reprodutivo, já o tamanho do bico está relacionado positivamente.

Sexual selection is a force that limits the access of individuals of a sex to the individuals of the opposite sex during the period of reproduction acting conspicuously in males and favoring morphological and behavioral treatments that increase reproductive success. Many bird species have large sex differences, but for many species considered monomorphic, there may be small differences between males and females. Motmots are considered monomorphic and the group is known to present a long and elaborate tail with racket apex. Its value on the recognition of the sexes and evolution of secondary sexual characters has not been researched yet. Thus, the general objective of this study is to verify the occurrence of secondary sexual characteristics in Momotus momota and to relate to reproductive success. Data collection was carried out during the reproductive period, from August to November 2017 and 2018. The pairs of birds with active nests were collected with mist net for weight measurement with precision scale and lengths with pachymeter or tape. The recognition of the sexes was defined based on the result of the sexing examination. The results show that the males’ mass, area of the flag and black area of the flag are bigger and the size of the flag is negatively related to the reproductive success, while the beak size is related positively to the reproductive success.
Keywords: Cuidado parental; Dieta; Ninhego; Período reprodutivo; Parental care; Diet; Nestling; Reproductive period; Dimorfismo sexual; Sucesso reprodutivo; Medidas; Cauda; Bandeira; Sexual dimorphism; Reproductive success; Measures; Tail; Flag; CIENCIAS BIOLOGICAS